Evaluation of left cardiac chamber function with cardiac magnetic resonance and association with outcome in patients with systemic sclerosis - Butcher Steele C; Vos Jaqueline L; Fortuni Federico; Galloo Xavier; Liem Sophie IE; Bax Jeroen J; Delgado Victoria; Vonk Madelon C; van Leuven Sander I; Snoeren Miranda; El Messaoudi Saloua; de Vries-Bouwstra Jeska K; et al. (Oxford Univ Press, 2025)
Objective
This study aimed to determine whether lower values of feature-tracking cardiovascular magnetic resonance (CMR)-derived left atrial reservoir strain (LARS) and impaired left ventricular (LV) global longitudinal strain (GLS) were associated with the presence of symptoms and long-term prognosis in patients with SSc.
Methods
A total of 100 patients {54 [interquartile range (IQR) 46-64] years, 42% male} with SSc who underwent CMR imaging at two tertiary referral centres were included. All patients underwent analysis of LARS and LV GLS using feature-tracking on CMR and were followed-up for the occurrence of all-cause mortality.
Results
The median LV GLS was -21.8% and the median LARS was 36%. On multivariable logistic regression, LARS [odds ratio (OR) 0.964 per %, 95% CI 0.929, 0.998, P = 0.049] was independently associated with New York Heart Association (NYHA) class II-IV heart failure symptoms. Over a median follow-up of 37 (21-62) months, a total of 24 (24%) patients died. Univariable Cox regression analysis demonstrated that LARS [hazard ratio (HR) 0.94 per 1%, 95% CI 0.91, 0.97, P < 0.0001) and LV GLS (HR 1.10 per %, 95% CI 1.03, 1.17, P = 0.005) were associated with all-cause mortality, while LV ejection fraction was not. Likelihood ratio tests demonstrated that LARS provided incremental value over prognostically important clinical and imaging parameters, including late gadolinium enhancement.
Conclusion
In patients with SSc, LARS was independently associated with the presence of NYHA class II-IV heart failure symptoms. Although both LARS and LV GLS were associated with all-cause mortality, only LARS provided incremental value over all evaluated variables known to be prognostically important in patients with SSc.